Impact of Aspirin on clinical outcome in advanced HCC patients receiving sorafenib and regorafenib. Issue 6 (June 2021) - Casadei-Gardini, Andrea; Rovesti, Giulia; Dadduzio, Vincenzo; Vivaldi, Caterina; Lai, Eleonora; Lonardi, Sara; Fornaro, Lorenzo; Pretta, Andrea; Zagonel, Vittorina; Bernardini, Laura; Astara, Giorgio; D'Amico, Francesco E.; et al.
Abstract: Background and aim: The aim of our retrospective study is to evaluate the prognostic significance of aspirin in patients with advanced HCC treated with sorafenib. Methods: 304 patients with HCC, consecutively treated with sorafenib from May 2007 to September 2018, were included in the clinical study. Of Them 93 patients token aspirin. Progression-free survival (PFS)and overall survival (OS)were estimated with the Kaplan–Meier method and compared with the log-rank test. Results: The concomitant use of sorafenib and aspirin was associated with a median OS of 18.3 months compared to 8.8 months of patients who did not receive aspirin (HR 0.57; P < 0.0001). The concomitant use of sorafenib and aspirin was associated with a median PFS of 7.3 months compared to 3.0 months of patients who did not receive aspirin (HR 0.61; P = 0.0003). In the multivariate analysis, the use of aspirin maintained an independent prognostic value for OS(HR 0.61; P = 0.0013). In second line the concomitant use of regorafenib and aspirin was associated with a median OS of 16.9 months compared to 8.0 months of patients who did not receive aspirin (HR 0.30; P = 0.02). Conclusion: Globally, our data seem to suggest that aspirin use may improve the clinical outcome of patients with advanced hepatocellular carcinoma receiving sorafenib and regorafenib.